Laboratory evidence on a direct correlation between acute central serous chorioretinopathy and tenascin C, metalloprotein 1, BAX, BCL2, subfatin and asprosin - Celik, F.; Coteli, E.; Gul, F. C.; Ozsoy, E.; Kobat, S. Gungor; Akkoc, R. F.; Aydin, S. (Masson Editeur, 2022)
Central serous chorioretinopathy (CSCR) is an eye disease of unknown etiology that presents with reduced visual acuity, choroidal thickening (distance between Bruch's membrane and the chorioscleral border), and subretinal fluid leakage. In the present study, the goal was to investigate the role of the interrelated tenascin C, metalloprotein-1, BAX, BCL2, subfatin and asprosin molecules in the pathogenesis of CSCR. Method. - Thirty CSCR patients and 30 controls were included. CSCR was diagnosed by optical coherence tomography imaging. A 5 mL blood sample was collected from all participants after overnight fasting. Compounds in the blood samples were studied with the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results. - Patients with CSCR were found to have macular thickening (P: 0.08) and statistically significantly reduced visual acuity (P: 0.034) compared to controls. With regard to serum parameters, there were statistically significant increases in tenascin C, metalloprotein-1, BAX, BCL2, subfatin and asprosin levels compared to controls. We found a positive correlation between macular thickness and tenascin C (r + 0.670, P < 0.001), metaloprotein-1 (r + 0.714, P < 0.001), BAX, BCL2 (r + 0.771, P < 0.001), subfatin and asprosin levels and a negative correlation between visual acuity and tenascin C (r + 0.605 P < 0.001), metaloprotein-1 (r + 0.704, P < 0.001), BAX, BCL2 (r + 0.738, P < 0.001), subfatin and asprosin levels. Conclusion. - The molecules studied herein were negatively correlated with visual acuity and positively correlated with macular thickness, suggesting that these molecules might have a role in the pathogenesis of CSCR. Thus, we predict that these molecules could be new candidates for the diagnosis and follow-up of CSCR in the future. (c) 2021 Published by Elsevier Masson SAS.
Preuves biologiques démontrant la corrélation directe entre la choriorétinopathie séreuse centrale aiguë et la ténascine C, la métalloprotéine 1, BAX, BCL2, la subfatine et l'asprosine
Keywords: Central serous chorioretinopathy; Tenascin C; Metalloprotein-1; BAX; BCL2; Subfatin; Asprosin